Effectiveness of interventions for reducing TB incidence in countries with low TB incidence: a systematic review of reviews. (29th May 2019) - Collin, Simon M.; Wurie, Fatima; Muzyamba, Morris C.; de Vries, Gerard; Lönnroth, Knut; Migliori, Giovanni Battista; Abubakar, Ibrahim; Anderson, Sarah R.; Zenner, Dominik
Aims: What is the evidence base for the effectiveness of interventions to reduce tuberculosis (TB) incidence in countries which have low TB incidence? Methods: We conducted a systematic review of interventions for TB control and prevention relevant to low TB incidence settings (<10 cases per 100 000 population). Our analysis was stratified according to "direct" or "indirect" effects on TB incidence. Review quality was assessed using AMSTAR2 criteria. We summarised the strength of review level evidence for interventions as "sufficient", "tentative", "insufficient" or "no" using a framework based on the consistency of evidence within and between reviews. Results: We found sufficient review level evidence for direct effects on TB incidence/case prevention of vaccination and treatment of latent TB infection. We also found sufficient evidence of beneficial indirect effects attributable to drug susceptibility testing and adverse indirect effects (measured as sub-optimal treatment outcomes) in relation to use of standardised first-line drug regimens for isoniazid-resistant TB and intermittent dosing regimens. We found insufficient review level evidence for direct or indirect effects of interventions in other areas, including screening, adherence, multidrug-resistant TB, and healthcare-associated infection. Discussion: Our review has shown a need for stronger evidence to support expert opinion and country experience when formulating TB control policy. Whilst vaccination and treatment of latent TB infection are supported by review level evidence, there is a need for a stronger evidence base in other intervention areas to support decisions when formulating TB control policy in low-incidence countries. http://ow.ly/Y4vA50p4Hfv